CONTRIBUCION AL ESTUDIO DE NIDOS INVERNANTES DE VESPULA GERMANICA (F.) (HYMENOPTERA: VESPIDAE) EN LA ZONA CENTRAL DE CHILE - Chiappa T., Elizabeth; Jopia R., Hermán; Morales L., Cecilia; Cook L., Jenny (Acta Entomológica Chilena, 2022)
Eight overwintering colonies were studied in the Central part of Chile. The following features, were observed: nests larger than the annual ones, polygyny, no protandry; a large number of males, most of them with the abdomen as large as the queen’s; disorder in the construction of the last floors. During the 3 years of observation the weather was unusually mild and dry; all the nest sites were protected and with good drainage. The importance of this type of colony as an individual advantage of the resource exploitaüon and the stablishment of better conditions for the eusociality is discussed.